Physical compatibility of insecticides and fungicides and their phytotoxicity on castor: Physical compatibility of insecticides and fungicides and their phytotoxicity on castor - G MADHURI; P DURAIMURUGAN; V DIVYA RANI; K SADAIAH; G NEELIMA; M RAJASHEKAR; CH V DURGA RANI; G ANURADHA; M VENKATA RAMANA (Journal of Oilseeds Research, 2020)
All 18 combinations of insecticides and fungicides tested were physically compatible. The combinations viz., novaluron + carbendazim, acetamiprid + carbendazim, acetamiprid + carbendazim 12% + mancozeb 63% and buprofezin + carbendazim 12% + mancozeb 63% showed phytotoxic symptoms like vein clearing and scorching on leaves, remaining all other treatment combinations were compatible.